Ultradeep targeted sequencing of circulating tumor DNA in plasma of early and advanced breast cancer. Issue 1 (4th November 2020) - Chin, Yoon Ming; Takahashi, Yoko; Chan, Hiu Ting; Otaki, Masumi; Fujishima, Makoto; Shibayama, Tomoko; Miki, Yoshio; Ueno, Takayuki; Nakamura, Yusuke; Low, Siew‐Kee
Abstract: We present a study to evaluate the feasibility and clinical utility of amplicon‐based Oncomine Pan‐Cancer cell‐free assay to detect circulating tumor DNA (ctDNA) in patients with early or advanced breast cancer. In this study, 109 early and metastatic breast cancer patients were recruited before the initiation of treatment. ctDNA mutation profiles were assessed through unique molecular tagging (UMT) and ultradeep next generation sequencing (NGS). For patients with mutations, DNA from corresponding white blood cells (WBC) was sequenced to exclude variants of clonal‐hematopoietic (CH) origin. UMT targeted sequencing from plasma of 109 patients achieved a median total coverage of 55 498X and a median molecular coverage of 4187X. Among 53 ctDNA positive samples, 38% were mutation positive by WBC sequencing, indicating potentially false‐positive results contributed by CH origin. Prevalence of CH‐related mutations was associated with age ( P  = 7.51 × 10 −4 ). After exclusion of CH mutations, ctDNA detection rates were 37% for local or locally advanced breast cancer (stage I‐III) and 81% for metastatic or recurrent breast cancer. The ctDNA detection rate correlated with disease stage ( P  = 2.60 × 10 −4 ), nodal spread ( P  = 6.49 × 10 −3 ) and the status of distant metastases ( P  = 5.00 × 10 −4 ). ctDNA variants were detected mostly in TP53, PIK3CA and AKT1 genes, with variants showing therapeutic relevance. This pilot study endorses the use of targeted NGS for non‐invasive molecular profiling of breast cancer. Paired sequencing of plasma ctDNA and WBC should be implemented to improve accurate interpretation of liquid biopsy. Abstract : We present a study to evaluate the feasibility and clinical utility of amplicon‐based liquid biopsy assay to detect circulating tumor DNA (ctDNA) in patients with early or advanced breast cancer. After excluding CH mutations, the ctDNA detection rate correlated with disease stage, nodal spread and the status of distant metastases. Paired sequencing of plasma ctDNA and WBC should be implemented to improve accurate interpretation of liquid biopsy.